(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many States are failing to keep the momentum up in pushing the growth rate either because their social capacity is not up to the brim and people are struggling to get two ends meal. What the States are needed to keep continuing with investment at ever increasing rate and deal social priorities differently? There are many States which face the wrath of anti-incumbency every five years the reason for this larger section of the people remain untouched with the development schemes. It is their bad luck that neither did they get the benefit of moving up in the social hierarchy nor they are covered with some employment guarantee scheme. The vulnerability during the pandemic have further added the burden of making the people socially strong. Education and health both have gone through serious setback.